Tribological coatings for electric vehicle applications - Lee, Seungjoo; Farfan-Cabrera, Leonardo Israel; Berman, Diana; Rosenkranz, Andreas; Erdemir, Ali (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
Electric vehicles (EVs) represent a new paradigm for a sustainable transportation future with the potential to offer unparalleled energy security, environmental cleanliness, and economic prosperity for all humanity. However, rapid development and adaptation of this new transportation approach depend on addressing multiple challenges, including the development of new materials and coatings that can meet the more stringent thermal, electrical, and tribological requirements of EV drivetrains. Specifically, the operating conditions of moving mechanical assemblies (i.e., bearings, gears, among others) in EVs differ radically from those found in conventional internal combustion (IC) engines -thus giving rise to notable reliability issues. In particular, as the function of bearings and gear systems shift from mostly loadcarrying (in IC engines) to the torque-transferring mode in EVs, durability concerns of these assemblies due to severe deformation, wear, micro-pitting, fatigue, and scuffing may worsenas electric motors can generate maximum torque at near zero speeds but maximum efficiency at around 90% speed (this is opposite of conventional IC engines, which generate high torques at high speeds). These conflicting requirements require a different set of lubricant-material combinations to circumvent such problems under high loads and low-speed conditions of EVs. Therefore, new materials, coatings, and lubrication strategies need to be developed and implemented for future EVs to become tribologically viable and reliable. Accordingly, EV drivetrains can potentially benefit from advanced functional coatings that have already significantly improved the functionality of moving components of IC engines. The main objective of this article is to draw attention to some of the tribological issues in EVs and how advanced functional coatings can help resolve these issues due to their unique thermal, electrical, mechanical, and tribological properties, ultimately making EVs more durable and reliable.